Presence of antibodies against Leptospira spp in homes with cats and humans in a neighbourhood of Medellín, Colombia - Isaza Molina, Daniela (2020)
This study aimed to identify the presence of antibodies against Leptospira spp in felines and humans living in the same house of the Nueva Villa de La Iguaná neighborhood, part of the Comuna 7 of Medellín, Colombia, between November and December 2018. Historical data from the area indicate a seroprevalence of 63.2% in humans. Through a cross-sectional study in the neighborhood, 30 homes were selected where 30 people and 32 cats lived together. A survey was applied, and blood samples were collected to detect antibodies against Leptospira spp using the microagglutination test (MAT). The seroreactive results against Leptospira spp in cats and humans were negative for leptospirosis, which suggests that the felines in the neighborhood have a protective role against Leptospira spp in their owners.